1599 Review of Telephone Consultations for Suspected Head and Neck Cancer Referrals During The COVID-19 Pandemic. (12th October 2021) - Suresh, A; Goel, A; Khan, N; Promod, P; Pabla, R; Cymerman, J
Abstract: Introduction: Pandemic COVID-19 necessitated a transformation in the delivery of healthcare. Telephone consultations were introduced to protect and progressively manage patients with minimal delay. This is a review of the effectiveness of these remote consultations for suspected 2-week wait (2ww) head and neck cancer referrals to a north London NHS teaching hospital Oral and Maxillofacial unit during the first official UK government lockdown from March - July 2020. Method: Prospective electronic records of 176 consecutive 2ww referrals between March – July 2020 was assessed. Data analysed included initial telephone consultations, subsequent face-to-face (F2F) appointments, if required, the interval from telephone to F2F appointments and histopathological diagnoses. Results: 157 patients (n = 176) received an initial telephone call, of which 127 (80.9%) required a F2F consultation. The number of days between the initial telephone consultation and subsequent F2F assessment ranged from 0 to 141, with a mean of 11 and a median of 1. Notably, 31 patients (24.4%) were seen in person on the same day as their telephone consultation. Biopsies were indicated for 69 patients (54.3%) of which 9 (13.0%) were diagnosed as malignancies. Conclusions: Whilst protecting patients from a pandemic is utmost, continuing care for non-pandemic conditions must be considered. It is even more important to manage 2ww referrals efficiently. These results indicate the majority of suspected cancer referrals warrant F2F assessment for a confident outcome. Despite reinstated, ongoing social restrictions, 2ww referrals are now being seen exclusively F2F, subject to patient choice. This information is useful for planning and strategizing services in a head and neck OMFS unit.